Asymptomatic carriage of Streptococcus pneumoniae detected by qPCR on the palm of hands of populations in rural Senegal. - Codou Ndiaye; Hubert Bassene; Jean-Christophe Lagier; Didier Raoult; Cheikh Sokhna (Public Library of Science (PLoS), 2018)
Aside from malaria, infectious diseases are an important cause of death in sub-Saharan Africa and continue to pose major public health problems in African countries, notably pneumonia. Streptococcus pneumoniae remains the most common bacterial cause of pneumonia in all age groups. The skin is one of the main infection sites followed by the oropharynx. The skin carriage of certain pathogenic bacteria such as S. pneumoniae is often ignored or under-diagnosed. Finally, the mode of transmission of these infections remains uncertain. Here, we hypothesized that skin could play a role in the transmission of these infections. We collected 649 cotton swabs from a healthy population in Dielmo and Ndiop, rural Senegal. The sampling was carried out on the palm of the hands. After DNA extraction and actin control, qPCR targeting eight different bacteria was performed on 614 skin samples. We detected Streptococcus pneumoniae in 33.06% (203/614), Staphylococcus aureus in 18.08% (111/614) and Streptococcus pyogenes in 1.95% (12/614) of samples. A skin S. pneumoniae carriage was detected in more than a third of a rural population in rural Africa, highlighting the need to develop hand disinfection programs in order to reduce the burden of infections.